Characterization of the SCP/TAPS gene family in Drosophila melanogaster. - Kovalick, G.E.; Griffin, D.L. (Insect Biochemistry and Molecular Biology, 2005)
The SCP/Tpx-1/Ag5/PR-1/Sc7 (SCP/TAPS) gene family encodes proteins found in many eukaryotes. SCP/TAPS proteins are defined by the presence of an SCP/TAPS domain, and many participate in important physiological processes. Five SCP/TAPS genes were previously identified in Drosophila melanogaster and are expressed in the digestive tract or in the testes. Sequence databases were searched to determine if other SCP/TAPS genes were present in D. melanogaster, and an additional 21 SCP/TAPS genes were identified. To further define the roles of these genes, the structures of each gene and protein were analyzed. Based on these analyses, 25 SCP/TAPS genes could be placed into one of two groups. Each group contained conserved intron positions that were not shared with the other group. Proteins encoded by group 1 genes also shared additional sequence motifs and conserved cysteines not found in group 2 proteins. To determine if the two groups were expressed differently, reverse transcriptase (RT)-polymerase chain reaction (PCR) was used to examine expression in adult flies. The results indicated that most genes were preferentially expressed in adult males, suggesting a role for these genes in male reproduction. Members of both groups displayed this preferential expression, so it was not group-specific. The two groups may differ in localization rather than function.